(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2016)
The author singled out stages of implementation the antysypatyv management of ecological and economic system of enterprises. The author analyzes the main advantages and disadvantages of using the method of «decision tree» in the antysypatyv management. There are formed the antysypatyv management model ecological and economic system and test it in the target company.